Nasal Tip Delamination: A Technique for Nasal Tip Projection and Control in Rhinoplasty - Lisa Gfrerer, MD, PhD; Johanna N. Riesel, MD; Richard A. Bartlett, MD (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. Control of tip projection and rotation is critical to a successful rhinoplasty. Suture techniques that change the relationship of the medial crura to the caudal septum can effectively manage tip position, but may be technically challenging or require specialized sutures. The authors present a technique (“tip delamination”) that allows symmetrical exposure of the medial crura and caudal septum for accurate placement of projection control sutures using commonly available suture materials. Methods:. We describe a novel technique to completely expose (or delaminate) the medial crura of the lower lateral cartilages to allow for 360-degree access to and manipulation of these critical structures. We present a case series of 3 patients. Results:. Exemplary cases with 1 intraoperative video will be reviewed to demonstrate how tip delamination allows for more precise control of the medial crura and nasal tip. Conclusions:. Nasal tip delamination is a simple technique for manipulating the medial crura and nasal tip in rhinoplasty procedures. Nasal tip delamination adds minimal time and morbidity to the procedure and offers significant control for the surgeon, with beneficial outcomes for the patient.